2020
DOI: 10.1039/c9ra09240d
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ-based proteomic analysis reveals several key metabolic pathways associated with male sterility in Salvia miltiorrhiza

Abstract: Male sterility is a common phenomenon in flowering plants, and it has been widely used in hybrid seed production in a number of economically important crops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The samples that were cultivated under optimal conditions were used as a reference to identify the differential expression. We defined DEPs as those up-expressed > 1.2 or down-expressed < 0.8 with a p- value < 0.05 ( t -test, multiple testing correction) under each stress condition, which is the cutoff commonly used for iTRAQ-based proteomics analysis of both prokaryotes and eukaryotes ( Wang et al, 2016 , 2020 ; Cheng et al, 2017 ; Hou et al, 2019 ; Li et al, 2019 ). The details of the specific growth rates, maximum growth yields, and number of DEPs under each condition are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The samples that were cultivated under optimal conditions were used as a reference to identify the differential expression. We defined DEPs as those up-expressed > 1.2 or down-expressed < 0.8 with a p- value < 0.05 ( t -test, multiple testing correction) under each stress condition, which is the cutoff commonly used for iTRAQ-based proteomics analysis of both prokaryotes and eukaryotes ( Wang et al, 2016 , 2020 ; Cheng et al, 2017 ; Hou et al, 2019 ; Li et al, 2019 ). The details of the specific growth rates, maximum growth yields, and number of DEPs under each condition are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…As a staged tissue, the tapetum provides nutrients and energy for the maturation of microspore cells. In the omics studies of Chinese cabbage [ 47 ], salvia [ 48 ], rape [ 49 ], watermelon [ 50 ], and cotton [ 51 ], it has been found that the glycolysis/gluconeogenesis pathway has an essential function in the process of male sterility. Because the glycolysis/gluconeogenesis pathway produces many carbohydrates and various enzymes, it is closely related to plants’ average growth and development.…”
Section: Discussionmentioning
confidence: 99%